Prática docente nos cursos superiores de enfermagem do município de São José do Rio Preto SP - Alexandre, Kethi Cristina do Rosário Squecola (2014)
Introduction: The background and the pedagogical practice of teachers have an essential role to the former nursing student and for construction of educational action. Objectives: This study aimed to identify, analyze and relate the training and pedagogical practice in Undergraduate Nursing private and public institutions. Methods: A descriptive, correlational cross-sectional study using a quantitative approach using a questionnaire, which was answered by 107 teachers from private and public institutions of the inland of São Paulo State. Respondents were 60 teachers from private institutions and 47 teachers from a public institution. Data collection occurred from June to August 2013. Statistical analysis used the Statistical Package for Social Sciences (SPSS) for Windows ® version 22 and the chi-square and Fisher exact statistical tests were applied. Results: In the private institutions the teachers are predominantly female (76.7%) without a spouse (51.7%) age ranging from 31 to 50 years (60%), with more than one job (58.3%), master’s degree (41.7%), weekly working hours from 11 to 30 class load/hours with activities centered on education (40%) and planning of the discipline individually (55%). As for the difficulties in teaching practice reported by the teachers of private institutions, we found 26 (43.3%) institutional difficulties, with a prevalence of low pay, lack of support for research and infrastructure; 24 (40%) related to students, such as lack of interest and basic knowledge; 10 (16.7%) related to teaching, they reported lack of appropriateness of the content to the undergraduate student, excessive workload and another job. Regarding the types of evaluation, we found that 60 (100%) teachers of private institutions apply written tests. In the public institution, the teachers were women (100%), married (66%) aged over 50 years (63.8%) without another job (76.6%), working over 31 hours weekly classes (74.5%), doctors (61.7%), activities focused on education (68,52%), collective planning of the discipline (86%) and written exam as an assessment (89.4%). The difficulties of the teachers from the public institution, 36 (76.6%) were related to the teaching (lack commitment, interdisciplinary and theory-practice dichotomy), 8 (17%) about the lack of student interest, and only 3 (6 4%) reported institutional difficulties. There were significant differences in the background and pedagogical practice of teachers of private and public institutions regarding age, duration of teaching, workload, more than one job, degree, course planning, teaching techniques and diverse types of reviews. There was a similarity in relation to the participation of teachers in continuing education, teacher training and more hours devoted to teaching. Conclusion: The private and public institutions, despite being from the same area showed different work processes. The results of this study provide grants to institutions of educational interventions for improvement of teachers in improving the quality of nursing education.